2014
DOI: 10.1038/ajg.2014.313
|View full text |Cite
|
Sign up to set email alerts
|

Oral Corticosteroids and the Risk of Serious Infections in Patients With Elderly-Onset Inflammatory Bowel Diseases

Abstract: We found an excess relative risk for serious infections in elderly-onset IBD patients on oral corticosteroid therapy. Those with current exposure demonstrated a higher vulnerability to infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 36 publications
4
79
0
9
Order By: Relevance
“…In the present patient series, CAP was performed in patients with moderate or severe UC that required hospitalization, and a high remission rate was achieved. In general, CAP has the advantage of causing only mild adverse effects . There were few adverse effects of CAP in either the present study's younger group or the elderly group, and all events were reversible.…”
Section: Discussionmentioning
confidence: 45%
“…In the present patient series, CAP was performed in patients with moderate or severe UC that required hospitalization, and a high remission rate was achieved. In general, CAP has the advantage of causing only mild adverse effects . There were few adverse effects of CAP in either the present study's younger group or the elderly group, and all events were reversible.…”
Section: Discussionmentioning
confidence: 45%
“…It should be noted that steroids are not suitable for maintenance therapy but are highly effective in remission induction. In the real world, patients with steroid dependency are treated with steroids for an extended period, and the associated adverse reactions are a concern [25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid use is a marker of active intestinal inflammation, which predisposes to infection. To make a more direct association between corticosteroids and infection, the authors showed a time-dependent risk of serious infection, with more recent corticosteroid use associated with the highest vulnerability to infection [50]. In another study evaluating 100 consecutive IBD patients with opportunistic infections, increasing age was a risk factor for infection.…”
Section: Moderate-severe Diseasementioning
confidence: 96%